Effect of unwanted guest molecules on the stacking configuration of covalent organic frameworks: a periodic energy decomposition analysis - Wonanke, A. D. Dinga; Addicoat, Matthew A (Physical chemistry chemical physics : PCCP, 2022)
Elucidating the precise stacking configuration of a covalent organic framework, COF, is critical to fully understand their various applications. Unfortunately, most COFs form powder crystals whose atomic characterisations are possible only through powder X-ray diffraction (PXRD) analysis. However, this analysis has to be coupled with computational simulations, wherein computed PXRD patterns for different stacking configurations are compared with experimental patterns to predict the precise stacking configuration. This task is often computationally challenging firstly because, computation of these systems mostly rely on the use of semi-empirical methods that need to be adequately parametrised for the system being studied and secondly because some of these compounds possess guest molecules, which are not often taken into account during computation. COF-1 is an extreme case in which the presence of the guest molecule plays a critical role in predicting the precise stacking configuration. Using this as a case study, we mapped out a full PES for the stacking configuration in the guest free and guest containing system using the GFN-xTB semi-empirical method followed by a periodic energy decomposition analysis using first-principles Density Functional Theory (DFT). Our results showed that the presence of the guest molecule leads to multiple low energy stacking configurations with significantly different lateral offsets. Also, the semi-empirical method does not precisely predict DFT low energy configurations, however, it accurately accounts for dispersion. Finally, our quantum-mechanical analysis demonstrates that electrostatic-dispersion model suggested Hunter and Sanders accurately describes the stacking in 2D COFs as opposed to the newly suggested Pauli-dispersion model. Periodic energy decomposition analysis shows the accuracy of GFN-xTB vs. PBE-D3/TZ2P for the PES of empty and guest-containing COF-1.